Harnessing stem cells for regenerative medicine: Current applications and future prospects - Somayeh Shamlou; Hossein Rostami; Ali Hassanzadeh; Simin Rajaeian; Saeedeh Torabi Goudarzi; Mansour Arab; Ali Shojaeian; Javad Verdi; Nasim Vousooghi (Journal of Clinical and Translational Research, 2026)
Background: Degenerative diseases place an immense burden on global healthcare. Stem cell-based regenerative medicine offers transformative, potentially curative therapies to restore damaged tissues and recover normal physiological function. Aim: This review aims to comprehensively evaluate the therapeutic applications, biological mechanisms, and clinical prospects of stem cells in treating diverse human organ disorders. Methods: We conducted a comprehensive literature review of preclinical models and clinical trials focusing on mesenchymal (MSCs), hematopoietic (HSCs), and pluripotent stem cells (PSCs), evaluating their efficacy, safety, and manufacturing challenges. Results: Cell therapies demonstrate remarkable healing potential. MSCs exhibit potent immunomodulatory effects in inflammatory conditions. HSC transplantation remains the gold standard for hematological disorders and is expanding into targeted gene therapies. PSC-derived cells show promising clinical efficacy in spinal cord injuries, macular degeneration, type 1 diabetes, and heart failure. However, significant hurdles remain, including immune rejection, tumorigenicity, and batch-to-batch variability. Conclusion: Cell therapies represent a paradigm shift from lifelong symptom management to definitive cures. Resolving biological, technical, and regulatory hurdles is imperative for the safe, standardized, and widespread clinical translation of these interventions. Relevance for Patients: For patients suffering from chronic, degenerative, or currently incurable conditions, stem cell therapies represent a transformative clinical paradigm. By facilitating functional tissue regeneration and targeted immunomodulation, these therapies reduce the burden of chronic pharmacotherapy and invasive procedures.